Kinetics research of the process of phosphorylation of regenerated cellulose in the system phosphoric acid – tributyl phosphate – phosphorus oxide(V) - Yurkshtovich, Nikolai K.; Golub, Natalia V.; Yurkshtovich, Tatyana L.; Mironchik, Violetta O.; Alinovskaya, Valentina A.; Kaputsky, Fedor N. (Journal of the Belarusian State University. Chemistry, 2017)
The regularities of the esterification reaction of cellulose in the system of phosphoric acid – tributyl phosphate – phosphorus oxide(V) with various ratios of reagents, reaction temperature and time were investigated. The quantitative assessment of the kinetic process was presented with the help of the polychronal kinetics equation. Based on the results of the equation, activation energy values, it was concluded that the rate-limiting step of the process is diffusion. Esterification of cellulose takes place in a heterogeneous environment and the rate of diffusion of agent to the cellulose fiber structure depends not only on the temperature and composition of the reaction mixture, but also on the structural features of the modified material, determining the availability of hydroxyl groups to esterification. Conditions for obtaining cellulose phosphate in the form of a hydrogel containing phosphate groups of up to11,2 % were optimized.